Piloting the Pioneer Positive Deviance (P-PD) approach for producer-led scaling in the pastoralist context of Dassenech Woreda, South Omo Zone, Ethiopia - Worku, Tigist; Habermann, Birgit; Getahun, Elizabeth; Knight-Jones, Theodore J.D.; Achandi, Esther L (International Livestock Research Institute, 2025)
Executive Summary In this scoping study we assessed the feasibility of implementing the Pioneer Positive Deviance (P-PD) approach for producer-led scaling in pastoralist communities in Dassenech Woreda, South Omo Zone, Ethiopia. We examined local pastoral systems, identified Positive Deviant (PD) practices and indicators related to animal health and feed management, consulted key stakeholders, and assessed opportunities and constraints for scaling locally-led adaptation practices. The study was a collaboration between the RESTORE Project and the Science Program for Sustainable Animal and Aquatic Foods (SAAF), combining social sciences with animal health, feed, and forage management expertise. The study covered two kebeles : Akodongole (agro-pastoral with irrigated fodder systems) and Doshe (dryland pastoral, rangeland-based). We collected data through stakeholder consultations at the zonal, woreda , and kebele levels using key informant interviews, community group discussions, field observations, and secondary sources. Dassenech Woreda is an arid and semi-arid pastoralist area with an estimated population of 86,000. Livelihoods rely mainly on livestock production (cattle, sheep, goats, camels, chickens), complemented by flood-recession agriculture, fishing, and emerging activities such as poultry, honey production, and small-scale trade. Communities face recurrent flooding, drought, livestock diseases, and displacement, yet demonstrate strong adaptive capacity and resilience. Women play a central, often under-recognized role in livestock care, feed management, and household resilience. In this study we identified a limited number of households, families or individuals exhibiting PD behaviors, achieving better livestock outcomes despite operating under similar constraints. These behaviors included animal health management, feed and fodder management, rangeland governance, rapid adoption of new practices, experimentation, and knowledge sharing. Positive deviant households and families demonstrated strong labor commitment, joint decision-making, and coordinated roles among men, women, and youth. Women were key in fodder collection, barn hygiene, and in taking care of sick and young animals. These indicators provide a practical basis for identifying pioneer families and households for subsequent phases of the P-PD approach that build on these practices for scaling among peers. Key opportunities for scaling locally-led adaptation practices include improved feed and fodder management, livelihood diversification, and animal health services. Constraints include limited extension services, frequent staff turnover, language barriers among extension agents (who often do not speak the local language), flood-related displacement, feed shortages, damaged infrastructure, limited youth engagement, and dependency on external aid. The findings confirm that implementation of the P-PD approach is feasible and relevant in Dassenech Woreda. Existing peer-learning traditions (NAP meetings, which is a traditional community evening meeting platform), community groups, Community Animal Health Workers (CAHW) networks, and women’s central role in livestock management provide a strong foundation for producer-led scaling. Successful implementation will require climate-resilient design, strong facilitation, gender-responsive approaches, and alignment with ongoing government and NGO initiatives. Key Take-Home Messages Positive deviance exists: Some households and families achieve better livestock health, fodder management, and productivity outcomes under the same constraints as others. Communities favor peer learning: Existing platforms such as NAP meetings, cooperatives, and CAHW networks provide natural entry points for P-PD. Women are critical agents of change: Livestock and feed management heavily rely on women’s labor and expertise. Climate shocks are central: Flooding and displacement disrupt feed systems, health services, and infrastructure, requiring flexible, mobile, and climate-resilient approaches. Institutional support is present but fragile: Government and NGO interventions exist but are affected by staff turnover, language barriers, and infrastructure gaps. Recommendations Identify and support pioneer households and families: Engage development agents (DAs), elders, and community leaders to identify PD households and families and provide demand-led training and improve understanding of their practices. Strengthen peer learning platforms: Use existing platforms to share and document PD practices.